2022
DOI: 10.1016/j.jjcc.2021.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neuromuscular electrical stimulation on functional capacity and quality of life among patients after cardiac surgery: A systematic review and meta-analysis

Abstract: Background: Neuromuscular electrical stimulation (NMES) is a possible adjunctive therapy applied to cardiac surgery patients to improve physical function, but the results are still controversial. A systematic review and meta-analysis was conducted to investigate the effects of NMES on functional capacity and quality of life (QoL) in cardiac surgery patients. Methods: The following databases PubMed, Embase, Medicine, CINAHL, and the Cochrane Central Register of Controlled Trials were searched for the English la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…We clarified the efficacy and adverse events of NMES following cardiovascular surgery more precisely than in a previous systematic review [ 13 ]. In the previous study, one quasi-RCT was included in a meta-analysis of knee extensor strength [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We clarified the efficacy and adverse events of NMES following cardiovascular surgery more precisely than in a previous systematic review [ 13 ]. In the previous study, one quasi-RCT was included in a meta-analysis of knee extensor strength [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review regarding the efficacy of NMES on lower limb muscle strength was reported after thoracic and cardiac surgery [ 13 ]. However, this systematic review meta-analyzed randomized controlled trials (RCTs) and a non-RCT, which may have introduced false estimates of effect sizes.…”
Section: Introductionmentioning
confidence: 99%